Expert consensus-building for developing guidelines: lessons learned from a dengue economics workshop - Dagna Constenla; Noah Lefcourt; Cristina Garcia (Pan American Health Organization, 2013)
A workshop with 20 experts of diverse backgrounds from five countries in the Americas was convened for two-and-a-half days in March 2012 to discuss and develop a standardized methodology for assessing the economic cost of dengue. This article discusses a number of factors that contributed to the workshop's success, including: engaging the experts at various stages of the process; convening a multidisciplinary group to reduce expert bias and provide a more comprehensive and integrated approach; facilitating guided small- and large-group discussions; developing effective cross-cultural collectivism, trust, communication, and empathy across the expert panel; establishing clear lines of responsibilities within each group of experts; breaking down the complex issues into smaller and simpler ideas; providing ample background materials in multiple languages prior to the workshop. Challenges and areas for improvement are also covered.